Spreading the 'burden'? a review of policies to disperse asylum seekers and refugees - Robinson, Vaughan 1957-; Andersson, Roger 1952-; Musterd, Sako 1953- (Policy Press, 2003)
This topical book outlines the expressed rationale for dispersal policies, reviews how such policies have been implemented in the UK, Netherlands and Sweden, identifies good practice and challenges the need for dispersal. Related titles include Doing Research with Refugees (Policy Press, 2006) and Refugee Community Organisations and Dispersal (Policy Press, 2005)
Title from publisher's bibliographic system (viewed on 20 Jan 2022)
Keywords: Refugees / Government policy / Great Britain; Refugees / Government policy / Netherlands; Refugees / Government policy / Sweden; Refugees / Civil rights / Great Britain; Refugees / Civil rights / Netherlands; Refugees / Civil rights / Sweden